A mixed‐methods study of cyclin‐dependent kinase 4 and 6 inhibitor symptom burden and quality of life among metastatic breast cancer patients and providers - Oswald, Laura B.; Arredondo, Brandy; Kadono, Mika; Martinez‐Tyson, Dinorah; Meade, Cathy D.; Penedo, Frank; Antoni, Michael H.; Soliman, Hatem; Costa, Ricardo L. B.; Jim, Heather S. L. (Cancer medicine (Malden, MA), 2021)
Background Cyclin‐dependent kinase 4 and 6 (CDK4/6) inhibitor targeted therapies dramatically improve survival outcomes for metastatic breast cancer (MBC), but they are associated with significant symptom burden that can impact patients’ health‐related quality of life (HRQOL) and treatment outcomes. This study is the first to describe CDK4/6 inhibitor symptoms from the lived perspectives of MBC patients taking CDK4/6 inhibitors and healthcare providers involved in MBC care. This study also explored patients’ symptom management and HRQOL concerns, and gathered feedback about developing supportive interventions for MBC. Methods MBC patients taking CDK4/6 inhibitors (N = 20) and MBC healthcare providers (N = 12) participated in semi‐structured interviews that were analyzed for qualitative themes. MBC patients completed surveys about HRQOL, symptoms, and unmet needs. Results Patient and provider perceptions of CDK4/6 inhibitor symptoms did not align with patients perceiving symptoms as more burdensome. Patients reported that supportive resources (e.g., support groups, blogs) that are not specific to MBC do not adequately meet their needs. Patients and providers were enthusiastic about developing supportive interventions specifically for MBC and offered considerations for designing such interventions. Conclusions Findings highlight differences in perceptions of CDK4/6 inhibitor symptom burden between MBC patients and providers. Results will inform the development of supportive interventions to assist MBC patients in managing CDK4/6 inhibitor symptom burden and maintaining HRQOL. Such interventions could also improve treatment outcomes. Metastatic breast cancer (MBC) patient and provider perceptions of symptoms associated with CDK4/6 inhibitor did not align, with patients perceiving symptoms as more burdensome. Patients reported that supportive resources (e.g., support groups, blogs) that are not specific to MBC do not adequately meet their needs, however patients and providers were enthusiastic about developing supportive interventions specifically for MBC and offered considerations for designing such interventions. Results will inform the development of supportive interventions to assist MBC patients in managing CDK4/6 inhibitor symptom burden and maintaining health‐related quality of life.